2012
DOI: 10.1007/s10900-012-9628-y
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Mixing, Drug Exchanges, and Infection Risk Among Long-Haul Truck Drivers

Abstract: Despite extensive anecdotal evidence on US long-haul truckers' risk interactions on the road, links between their sexual mixing and drug exchanges and their potential risk for STI/BBI acquisition and dissemination remain insufficiently documented. Grounded in social ecological theories and multi method ethnographic data, this paper examines the sexual transactions and drug exchanges of key members of US trucker risk networks within diverse trucking milieux. Research has uncovered four key trucker-centered popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…More recent statistics indicate that estimated deaths among tractor-trailer drivers with a blood alcohol concentration of 0.08 declined from 16% in 1982 to 2% in 2005 (Insurance Institute for Highway Safety, 2007), attributable to the drug and alcohol testing that became a requirement in the United States in 2001. Ongoing ethnographies corroborate truckers' farreaching use of amphetamines, cocaine, crack, and marijuana to stay awake and alert while driving, get high while partying, relax between trips, or improve sleep Apostolopoulos et al, 2010).…”
Section: Risk-laden Substance Use and Sexual Practicesmentioning
confidence: 86%
See 1 more Smart Citation
“…More recent statistics indicate that estimated deaths among tractor-trailer drivers with a blood alcohol concentration of 0.08 declined from 16% in 1982 to 2% in 2005 (Insurance Institute for Highway Safety, 2007), attributable to the drug and alcohol testing that became a requirement in the United States in 2001. Ongoing ethnographies corroborate truckers' farreaching use of amphetamines, cocaine, crack, and marijuana to stay awake and alert while driving, get high while partying, relax between trips, or improve sleep Apostolopoulos et al, 2010).…”
Section: Risk-laden Substance Use and Sexual Practicesmentioning
confidence: 86%
“…Published research indicates that substance misuse can be a significant problem for commercial drivers (Apostolopoulos et al, 2010;Crouch et al, 1993;Insurance Institute for Highway Safety, 2007;Korelitz et al, 1993). A study of 3,500 truckers attending a trade show found between 49% and 54% of participants smoked and 30% misused alcohol (Korelitz et al, 1993).…”
Section: Risk-laden Substance Use and Sexual Practicesmentioning
confidence: 99%
“…It was also paradoxical that while most participants said it was easier to negotiate condom use online, few engaged in this behavior. Rather, condom use and other safer sex practices were typically negotiated in face-to-face contexts and driven by perceived partner risks well-described in previous literature (e.g., Apostolopoulos, Sönmez, & Massengale, 2013; Benotsch et al, 2011; Seal & Ehrhardt, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the rapid spread of STIs within the population and becomes a much broader public health and safety issue, much of it is attributed to the mobility involved with the profession. Drivers are in different cities daily which creates situations in which STIs can be spread to other truckers and sexworkers but also spouses and committed partners as well (Apostolopoulos et al, 2010(Apostolopoulos et al, , 2013Lichtenstein et al, 2008).…”
Section: Whpmentioning
confidence: 99%
“…LHTDs are well documented for poor lifestyles (dietary intake, physical inactivity, smoking, alcohol consumption), and in turn elevated obesity rates and associated cardio-metabolic conditions (diabetes, metabolic syndrome, hypertension, cardiovascular disease) (Apostolopoulos et al, 2010(Apostolopoulos et al, , 2012a(Apostolopoulos et al, , 2014aHelmkamp et al, 2013;Jain et al, 2006;Seiber et al, 2014). Risky sexual behavior and subsequent increased risk for sexually transmitted infections (STIs) along with the linkage to substance abuse has been extensively reported (Apostolopoulos et al, 2010(Apostolopoulos et al, , 2013(Apostolopoulos et al, , 2015Lichtenstein et al, 2008;McCree et al, 2010). Mental illness is a frequent problem among truckers (Shattell et al, 2010), while fatigue and sleep restriction pose serious risks in the form of abnormal circadian rhythm influences on metabolic and hormonal imbalances and an increased risk for traffic and other work-related accidents (Moreno et al, 2006;Philip and Åkerstedt, 2006).…”
Section: Introductionmentioning
confidence: 99%